PENGARUH EKSPERIMEN SEDERHANA TERHADAP KEMAMPUAN MENGKLASIFIKASIKAN BENDA DI TK ISLAM INSAN MULIA MOJOKERTO - Permata Lestari, Sherfi Sulfiah; Naili Sa’id; Wahono; Tri Kurniawati (Bunayya, 2026)
This study aimed to examine the effect of simple experiment activities on the ability to classify objects among children aged 4–5 years at TK Islam Insan Mulia Mojokerto. The simple experiment was conducted in five sessions, each lasting 30 minutes. During the activities, children classified objects based on their properties in water, specifically whether the objects sank or floated. This study employed a quantitative approach using a quasi-experimental design with a pretest–posttest control group design. The participants consisted of 30 children aged 4–5 years, divided into an experimental group and a control group, with group assignment conducted non-randomly based on existing classes. Data were collected through a performance based classification task, in which children grouped objects according to the results of the sinking and floating experiments, and their performance was assessed using an observation sheet comprising five indicators of classification ability. Data analysis included descriptive and inferential analyses using an independent t-test on gain scores between the two groups. The results showed that the experimental group demonstrated a greater improvement in object classification ability than the control group. The mean gain score of the experimental group (M = 3.40; SD = 1.06) was higher than that of the control group (M = 0.33; SD = 1.18). The independent t-test revealed a significant difference (p < 0.001) with a very large effect size (Cohen’s d = 2.75). Therefore, it can be concluded that simple experiment activities have a significant effect on improving children’s object classification ability.